2016
DOI: 10.1104/pp.16.01734
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Modulates Histone Acetylation at Stress Genes by Inhibition of Histone Deacetylases

Abstract: Histone acetylation, which is an important mechanism to regulate gene expression, is controlled by the opposing action of histone acetyltransferases and histone deacetylases (HDACs). In animals, several HDACs are subjected to regulation by nitric oxide (NO); in plants, however, it is unknown whether NO affects histone acetylation. We found that treatment with the physiological NO donor S-nitrosoglutathione (GSNO) increased the abundance of several histone acetylation marks in Arabidopsis (Arabidopsis thaliana)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 96 publications
(128 reference statements)
6
86
0
Order By: Relevance
“…A recent integrative study reported that pathogen-triggered SA signaling induced the biosynthesis of NO, a molecule that physically inhibits several HDACs, including HDA19. Consequently, such inhibition leads to elevated acetylation levels in several SA defense genes and their transcription [81], a phenomenon that correlates with the described negative role of this HDAC over SA-mediated defense. It has been proposed that histone acetylation positively regulates SA-mediated defenses, since most of the plant HDAC mutants studied so far have been reported to be more resistant to at least one biotrophic or hemibiotrophic pathogen, including the rice deacetylase HDT701 [47,82].…”
Section: Defense and Epigeneticsmentioning
confidence: 62%
“…A recent integrative study reported that pathogen-triggered SA signaling induced the biosynthesis of NO, a molecule that physically inhibits several HDACs, including HDA19. Consequently, such inhibition leads to elevated acetylation levels in several SA defense genes and their transcription [81], a phenomenon that correlates with the described negative role of this HDAC over SA-mediated defense. It has been proposed that histone acetylation positively regulates SA-mediated defenses, since most of the plant HDAC mutants studied so far have been reported to be more resistant to at least one biotrophic or hemibiotrophic pathogen, including the rice deacetylase HDT701 [47,82].…”
Section: Defense and Epigeneticsmentioning
confidence: 62%
“…Experiments with TSA also suggest that histone acetylation plays a role in SE control [174], and the TSA-mediated inhibition of HDACs results in histone hyperacetylation and conformational changes of the chromatin-associated with enhanced gene expression [175]. Consistently, an increase in the H3K9/K14Ac and H4K5Ac epigenetic markers was reported in the TSA-treated seedlings of Arabidopsis [176,177]. In support of a role of histone acetylation in controlling SE induction, TSA treatment promoted the development of embryogenic structures on the seedlings and in vitro-cultured explants of Arabidopsis and conifers [22,23,178,179] and the beneficial effects of TSA on microspore cultures of T. aestivum [180] and B. napus [181] were reported.…”
Section: Histone Acetylationmentioning
confidence: 66%
“…Numerous studies have characterized different genes from the Arabidopsis KDAC families over the last two decades (Shen et al, 2015). In particular, HDA6, HDA9, and HDA19 from class I are the most well studied Arabidopsis KDACs and they have been implicated in many important developmental processes such as seed germination, flowering time, as well as plant hormone-related stress responses (Zhou et al, 2005;Benhamed et al, 2006;Chen et al, 2010;Choi et al, 2012;Cigliano et al, 2013;Zheng et al, 2016;Mengel et al, 2017). In terms of protein targets for deacetylation, very little is known about the preferences and targets of the different plant KDACs.…”
Section: Introductionmentioning
confidence: 99%